Composite hydrogen transfer catalyst based on MOFs (Metal-Organic Frameworks) material as well as preparation method and application of composite hydrogen transfer catalyst

By loading an active metal and a solid base onto MOF materials to form a composite hydrogen transfer catalyst, the problems of insufficient catalytic activity and low stability in the preparation of Guerbert alcohols were solved, achieving efficient and selective preparation of Guerbert alcohols while reducing energy consumption and environmental impact.

CN121446544APending Publication Date: 2026-02-03JIUJIANG DESI PHOTOELECTRIC MATERIALS CO LTD +1

Patent Information

Application Number
CN202511890049.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing catalysts for the preparation of Gelbert alcohols suffer from insufficient catalytic activity, poor selectivity, low stability, and harsh reaction conditions, making it difficult to meet the requirements of green chemistry and sustainable development.

Method used

A composite hydrogen transfer catalyst based on MOFs materials is used, which includes a supported active metal component and a solid base. The active metal component is loaded onto the MOFs material by impregnation or ion exchange, and the catalyst is prepared by ball milling or grinding to achieve uniform dispersion and high stability of the active metal.

Benefits of technology

The mild reaction conditions improved the yield and purity of Gelbert alcohol, reduced energy consumption and cost, and the catalyst can be reused, which is in line with the development concept of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a composite hydrogen transfer catalyst based on an MOFs material as well as a preparation method and application of the composite hydrogen transfer catalyst. The composite hydrogen transfer catalyst comprises the MOFs material loaded with an active metal component and solid alkali, the active metal component is selected from at least one of palladium, platinum, ruthenium, rhodium and nickel; the active metal component accounts for 0.5-5% of the mass of the catalyst; the MOFs material is selected from at least one of ZIF-8, MIL-101, UiO-66, HKUST-1 and MOF-5 (Metal Organic Frameworks); the solid alkali is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite and barium oxide. The catalyst provided by the invention has the advantages of high catalytic activity, good selectivity, strong stability, reusability and the like, can efficiently catalyze fatty alcohol to perform hydrogen transfer reaction under a lower-temperature reaction condition to prepare Guerbet alcohol, remarkably improves the yield and purity of a product, and reduces the reaction energy consumption and cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic synthesis catalysis technology, and particularly relates to a composite hydrogen transfer catalyst based on MOFs materials, its preparation method and application. Background Technology

[0002] Guerbet alcohol, also known as 2-alkyl-1-alkanol, is a class of higher fatty alcohols with a unique branched structure. The presence of branches in its molecular structure endows it with excellent physicochemical properties, such as low freezing point, high stability, and excellent lubricity, making it widely used in cosmetics, lubricants, high-end surfactants, inks, and pharmaceutical intermediates.

[0003] Currently, the preparation of Guerbert alcohols mainly uses aliphatic alcohols containing β-H as raw materials, achieved through the classic Guerbert reaction. This reaction typically includes four steps: dehydrogenation of the alcohol to an aldehyde, condensation of the aldehyde to a β-hydroxy aldehyde, dehydration of the β-hydroxy aldehyde to an α,β-unsaturated aldehyde, and hydrogenation of the α,β-unsaturated aldehyde to form Guerbert alcohol. In this process, the performance of the catalyst directly determines the microscopic mechanism, efficiency, selectivity, and product yield of the reaction; therefore, developing a suitable catalyst system is crucial.

[0004] Traditional Goerbert reaction catalysts are mainly divided into two categories: homogeneous catalysts and heterogeneous catalysts. Homogeneous catalysts, such as strong bases (sodium hydroxide, potassium hydroxide, etc.) or metal salts (such as platinum salts, palladium salts, etc.), although possessing high catalytic activity, suffer from problems such as difficulty in separation, inability to be reused, easy product contamination, and generation of large amounts of waste liquid leading to heavy metal pollution. For example, the presence of homogeneous bases such as potassium hydroxide and sodium hydroxide makes products and intermediates prone to saponification, increasing by-products. At the same time, these by-products poison the metal catalyst, making recovery difficult and resulting in waste. In addition, the use of homogeneous bases and the generation of soap by-products necessitate the use of strong acid cleaning in post-treatment steps, placing significant pressure on subsequent wastewater treatment and failing to meet the requirements of green chemistry and sustainable development. Heterogeneous catalysts, such as supported metal catalysts (supporting metals like Pd, Pt, and Ni on supports like alumina, silica, and activated carbon), have solved the problem of separation and recovery of homogeneous catalysts, but still have the following shortcomings: First, the catalytic active sites are not uniformly dispersed, resulting in low reaction selectivity and easy generation of byproducts (such as olefins and ethers); second, the catalyst has poor stability and is prone to metal particle agglomeration or loss during the reaction, leading to a decrease in catalytic activity; third, the reaction usually needs to be carried out under high temperature and high pressure conditions, resulting in high energy consumption and demanding requirements for reaction equipment.

[0005] CN 101659597A discloses a method using KOH as a base and nickel powder as a co-catalyst, requiring a pressure of 0.2-2 MPa and nitrogen protection to reduce oxidation byproducts and improve yield. US005777183A discloses a reaction requiring 245°C for the preparation of Gelbert alcohol. When decanol is used as a raw material, this temperature can only be reached when the dimer reaches 60%, and byproducts trimer and soap are produced. The reaction pressure must be controlled, and the catalyst should be dissolved in alkali metal hydroxide or alkaline earth metal hydroxide beforehand to shorten the reaction time and improve product quality. US8779216B2 discloses a method for preparing Gelbert alcohol using (a) a base, particularly an aqueous solution of potassium hydroxide, (b) a carbonyl compound, and (c) a hydrogenation catalyst (H) selected from metals ruthenium, rhodium, palladium, osmium, iridium, and platinum, wherein the metal is fixed on a hydrophobic support to prevent leaching.

[0006] Hydrogen transfer reactions, as a mild hydrogenation / dehydrogenation method, can achieve the hydrogenation of unsaturated compounds or the dehydrogenation of alcohols using hydrogen donors (such as isopropanol and formic acid) without the need for an external hydrogen source. They offer advantages such as mild reaction conditions, simple operation, and high safety. However, current catalysts used in hydrogen transfer reactions still suffer from insufficient activity, poor selectivity, and low stability, limiting their application in the preparation of Guerbert alcohols.

[0007] Metal-organic frameworks (MOFs) are a class of porous crystalline materials with periodic network structures, formed by the self-assembly of metal ions or metal clusters with organic ligands through coordination bonds. MOFs possess unique advantages such as large specific surface area, tunable pore structure, abundant and uniformly dispersed active sites, high chemical stability, and ease of functionalization, demonstrating enormous application potential in catalysis. Using MOFs as hydrogen transfer catalysts in the preparation of Guerbert alcohols can, on the one hand, leverage their abundant active sites and high specific surface area to enhance catalytic activity and selectivity, reducing side reactions; on the other hand, the controllable porous structure and high stability of MOFs facilitate catalyst recovery and reuse, aligning with the development principles of green chemistry. However, there are currently no reports on the use of MOFs as hydrogen transfer catalysts for the catalytic preparation of Guerbert alcohols. Therefore, developing a highly efficient, highly selective, and recyclable hydrogen transfer catalyst based on MOFs and applying it to the preparation of Guerbert alcohols has significant theoretical and practical value. Summary of the Invention

[0008] In view of this, the purpose of this invention is to provide a composite hydrogen transfer catalyst based on MOFs materials, its preparation method and application. This catalyst has the advantages of high catalytic activity, good selectivity, strong stability and reusability. It can efficiently catalyze the hydrogen transfer reaction of fatty alcohols to prepare Guerbert alcohols under relatively low temperature reaction conditions, significantly improving product yield and purity, and reducing reaction energy consumption and cost.

[0009] This invention provides a composite hydrogen transfer catalyst based on MOFs materials, comprising MOFs materials supported on active metal components and a solid base;

[0010] The active metal component is selected from at least one of palladium, platinum, ruthenium, rhodium, and nickel; the active metal component accounts for 0.5% to 5% of the catalyst mass;

[0011] The MOFs material is selected from at least one of ZIF-8, MIL-101, UiO-66, HKUST-1, and MOF-5;

[0012] The solid alkali is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite, and barium oxide.

[0013] Preferably, the mass ratio of the solid alkali to the MOF material loaded with active metal components is (1:0.1) to (1:1).

[0014] Preferably, the active metal component is selected from ruthenium or palladium;

[0015] The MOFs material is selected from MIL-101 or UiO-66.

[0016] This invention provides a method for preparing the composite hydrogen transfer catalyst based on MOFs materials described in the above technical solution, comprising the following steps:

[0017] After drying the MOF material, it was mixed with an active metal precursor solution and stirred at room temperature for 2-6 hours. Then, a reducing agent was added, and the mixture was stirred at 30-60°C for 1-3 hours. After separation, a solid product was obtained.

[0018] The solid product was washed and then vacuum dried to obtain a hydrogen transfer catalyst based on MOFs materials.

[0019] The MOF-based hydrogen transfer catalyst is mixed with a solid base, ball-milled or ground, and then activated to obtain a MOF-based composite hydrogen transfer catalyst.

[0020] Preferably, the reducing agent is selected from one or more of sodium borohydride, hydrazine hydrate, and formaldehyde.

[0021] Preferably, the concentration of the active metal precursor solution is 0.001~0.1 mol / L;

[0022] The active metal precursor is selected from at least one of palladium chloride, chloroplatinic acid, ruthenium trichloride, rhodium chloride, and nickel nitrate.

[0023] Preferably, the activation temperature is 100~150℃ and the activation time is 1~2h.

[0024] This invention provides a method for preparing Guerbert alcohol using the MOF-based composite hydrogen transfer catalyst described above, comprising the following steps:

[0025] Fatty alcohol, solvent and MOF-based composite hydrogen transfer catalyst were mixed, and the air was replaced with nitrogen. The mixture was reacted at 80-150℃ for 4-12 h. After the reaction was completed, the mixture was cooled, separated, and the collected filtrate was distilled under reduced pressure to obtain the crude product. After purification, Goerbert alcohol was obtained.

[0026] Preferably, the fatty alcohol is selected from one or more of n-hexanol, n-octanol, n-decanol, n-dodecanol, and n-tetradecylol;

[0027] The mass ratio of the fatty alcohol to the solvent is (1:0.01) to (1:1).

[0028] Preferably, the vacuum degree of the reduced pressure distillation is 0.08~0.095MPa, and the temperature is 100~150℃;

[0029] Purification was performed using silica gel as the stationary phase and a mixture of petroleum ether and ethyl acetate in a volume ratio of (10:1) to (20:1) as the eluent.

[0030] This invention provides a composite hydrogen transfer catalyst based on MOF materials, comprising MOF materials supported on an active metal component and a solid base; the active metal component is selected from at least one of palladium, platinum, ruthenium, rhodium, and nickel; the active metal component accounts for 0.5-5% of the catalyst mass; the MOF material is selected from at least one of ZIF-8, MIL-101, UiO-66, HKUST-1, and MOF-5; the solid base is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite, and barium oxide. The catalyst provided by this invention has advantages such as high catalytic activity, good selectivity, strong stability, and reusability. It can efficiently catalyze the hydrogen transfer reaction of fatty alcohols to prepare Guerbert alcohols under temperature reaction conditions, significantly improving product yield and purity, and reducing reaction energy consumption and cost. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the catalyst preparation process;

[0032] Figure 2 The GC spectrum of the Gerbert alcohol product (2-octyldodecyl alcohol);

[0033] Figure 3 This is the NMR spectrum of the Gerbert alcohol product (2-octyldodecyl alcohol). Detailed Implementation

[0034] This invention provides a composite hydrogen transfer catalyst based on MOFs materials, comprising MOFs materials supported on active metal components and a solid base;

[0035] The active metal component is selected from at least one of palladium, platinum, ruthenium, rhodium, and nickel; the active metal component accounts for 0.5% to 5% of the catalyst mass;

[0036] The MOFs material is selected from at least one of ZIF-8, MIL-101, UiO-66, HKUST-1, and MOF-5;

[0037] The solid alkali is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite, and barium oxide.

[0038] The composite hydrogen transfer catalyst based on MOFs materials provided by this invention includes MOFs materials loaded with active metal components; the MOFs materials serve as catalyst supports, and their rich pore structure and high specific surface area enable uniform dispersion of active metal components, significantly improving the catalytic activity and selectivity of the catalyst; at the same time, the excellent chemical and thermal stability of MOFs materials ensures that the catalyst is not prone to structural collapse or loss of active components during the reaction process, thus extending the service life of the catalyst.

[0039] This invention uses metal-organic frameworks (MOFs) as carriers to load active metal components into the pores or surface of MOFs via impregnation, ion exchange, or in-situ synthesis. The MOFs are selected from at least one of ZIF-8, MIL-101, UiO-66, HKUST-1, and MOF-5, preferably MIL-101 or UiO-66. MIL-101 and UiO-66 exhibit excellent chemical and thermal stability, and their porous structure facilitates the dispersion of the active metal components and the transport of reactants / products. The active metal component is selected from at least one of palladium (Pd), platinum (Pt), ruthenium (Ru), rhodium (Rh), and nickel (Ni), preferably ruthenium or palladium, as these two metals exhibit high catalytic activity and selectivity for hydrogen transfer reactions. The active metal component accounts for 0.5-5% of the catalyst mass; specifically, it can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4%, 4.5%, or 5%, preferably 1-3%. Within this loading range, the active metal component can be uniformly dispersed on the surface or in the pores of the MOF material, avoiding insufficient active sites due to too low loading or metal particle agglomeration due to too high loading, thereby ensuring that the catalyst has the best catalytic performance.

[0040] The composite hydrogen transfer catalyst based on MOFs materials provided by the present invention includes a solid base; the solid base is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite and barium oxide, preferably magnesium oxide or calcium oxide, because these two basic metal oxides have a large number of basic active centers, which is beneficial to improving the dehydrogenation rate.

[0041] In this invention, the mass ratio of the solid alkali to the MOF material loaded with active metal components is (1:0.1) to (1:1).

[0042] This invention provides a method for preparing the composite hydrogen transfer catalyst based on MOFs materials described in the above technical solution, comprising the following steps:

[0043] After drying the MOF material, it was mixed with an active metal precursor solution and stirred at room temperature for 2-6 hours. Then, a reducing agent was added, and the mixture was stirred at 30-60°C for 1-3 hours. After separation, a solid product was obtained.

[0044] The solid product was washed and then vacuum dried to obtain a hydrogen transfer catalyst based on MOFs materials.

[0045] The MOF-based hydrogen transfer catalyst is mixed with a solid base, ball-milled or ground, and then activated to obtain a MOF-based composite hydrogen transfer catalyst.

[0046] In this invention, MOF materials are dried and mixed with an active metal precursor solution, stirred at room temperature for 2-6 hours, then a reducing agent is added, and the mixture is stirred at 30-60°C for 1-3 hours. After separation, a solid product is obtained.

[0047] In this invention, the drying process of the MOFs material includes:

[0048] The MOFs material was placed in a vacuum drying oven and dried under vacuum at 80~120℃ for 6~12h to remove the moisture and impurities adsorbed in the pores of the MOFs material.

[0049] In this invention, the active metal precursor solution is prepared by dissolving the active metal precursor in a solvent to obtain the active metal precursor solution; the concentration of the active metal precursor solution is 0.001~0.1 mol / L; the active metal precursor is selected from at least one of palladium chloride (PdCl2), chloroplatinic acid (H2PtCl6·6H2O), ruthenium trichloride (RuCl3·3H2O), rhodium chloride (RhCl3·3H2O), and nickel nitrate (Ni(NO3)2·6H2O); the solvent is selected from deionized water, ethanol, or ethylene glycol.

[0050] The present invention preferably mixes MOF materials and active metal precursor solutions at room temperature, more preferably at 15~25°C, specifically 15°C, 20°C or 25°C; the mixing time is 2~6 hours, specifically 2 hours, 3 hours, 4 hours, 5 hours or 6 hours. Through the above mixing conditions, the active metal precursor is fully adsorbed into the pores or surface of the MOF materials.

[0051] The reducing agent used in this invention is selected from sodium borohydride, hydrazine hydrate, or formaldehyde. After adding the reducing agent, stirring is continued at 30-60°C for 1-3 hours, followed by separation to obtain a solid product. During continued stirring, the active metal precursor is reduced to elemental metal.

[0052] The present invention involves centrifuging or filtering the mixed solution obtained from the reaction to obtain a solid product.

[0053] This invention involves washing the solid product and then vacuum drying it to obtain a hydrogen transfer catalyst based on MOFs materials. Preferably, the solid product is washed 3-5 times with deionized water and ethanol respectively to remove residual impurities and reducing agents; then the solid product is placed in a vacuum drying oven; the drying temperature is 60-80℃, and the drying time is 6-12 hours to obtain the hydrogen transfer catalyst based on MOFs materials.

[0054] This invention involves mixing the aforementioned MOF-based hydrogen transfer catalyst with a solid base, followed by ball milling or grinding and activation to obtain a MOF-based composite hydrogen transfer catalyst. In this invention, the mass ratio of the MOF-based hydrogen transfer catalyst to the solid base is (1:0.1) to (1:1), and this ratio is adjusted according to the required alkalinity.

[0055] This invention can use a planetary ball mill with agate balls as the grinding medium, at a speed of 200-300 rpm for 1-2 hours, or by hand grinding with a mortar and pestle for 30-60 minutes to ensure uniform mixing of the powder.

[0056] The present invention preferably involves mild activation under a nitrogen atmosphere at a temperature of 100-150°C, specifically 100°C, 110°C, 120°C, 130°C, 140°C, or 150°C; and for a duration of 1-2 hours, specifically 1 hour, 1.5 hours, or 2 hours. Activation enhances the surface bonding between the solid base and the MOF-based hydrogen transfer catalyst.

[0057] The hydrogen transfer catalyst prepared by this invention exhibits excellent recyclability, allowing for multiple reuses and reducing catalyst waste and environmental pollution. Simultaneously, the solvent used in the reaction process is easily recovered and recycled, meeting the requirements of green chemistry and sustainable development. This invention effectively reduces the formation of byproducts and improves product purity by optimizing reaction conditions and employing column chromatography purification. Experimental results show that the final purity of the obtained Guerbert alcohol can reach over 98%, meeting the demand for high-purity Guerbert alcohol in the cosmetics and pharmaceutical industries.

[0058] This invention also provides a method for preparing Guerbert alcohol using the MOF-based composite hydrogen transfer catalyst described above, comprising the following steps:

[0059] A fatty alcohol, base, solvent, and MOF-based composite hydrogen transfer catalyst were mixed, and the air was replaced with nitrogen. The mixture was then reacted at 80-150°C for 4-12 hours. After the reaction was completed, the mixture was cooled, separated, and the collected filtrate was distilled under reduced pressure to obtain the crude product. The crude product was then purified to obtain Guerbert alcohol.

[0060] In this invention, the fatty alcohol is selected from one or more of n-hexanol, n-octanol, n-decanol, n-dodecanol, and n-tetradecyl alcohol; the base is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite, and barium oxide; and the solvent is selected from at least one of toluene, xylene, and cyclohexane. The mass ratio of the fatty alcohol to the solvent is (1:0.1) to (1:1). The composite hydrogen transfer catalyst based on MOFs material accounts for 0.05% to 2% of the mass of the fatty alcohol, specifically 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2%.

[0061] In this invention, the above mixing is carried out in a reactor. After mixing, the reactor is sealed; the bolts on the reactor flange are tightened diagonally using a wrench to ensure that the sealing gasket is completely compacted without any loose gaps; then, the pressure sensor and vacuum pipeline are connected to perform an airtightness test on the reactor. The pressure is slowly increased to 0.5 MPa at a rate of 0.1 MPa / min, and held for 10 min. The pressure change is observed. If the pressure drop is less than 0.01 MPa, the seal is considered qualified; otherwise, the sealing surface needs to be re-inspected and the sealing operation repeated. After the seal test, nitrogen is introduced to purge the air in the reactor 3-5 times.

[0062] Preferably, the reaction vessel is placed in an oil bath and heated to 80-150°C under stirring conditions, specifically 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C; the reaction time is 4-12 hours, specifically 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours; wherein, the stirring speed is 300-600 rpm.

[0063] After the reaction is completed, the reaction vessel is cooled to room temperature, the reaction vessel is opened, and the reaction mixture is centrifuged or filtered to separate the catalyst for recycling. The collected filtrate is distilled under reduced pressure to obtain the crude product, which is then purified to obtain Guerbert alcohol.

[0064] This invention removes the solvent and unreacted raw materials from the filtrate by vacuum distillation to obtain a crude product. The vacuum degree of the vacuum distillation is 0.08~0.095 MPa, specifically 0.08 MPa, 0.085 MPa, 0.09 MPa or 0.095 MPa; the temperature is 100~150℃, specifically 100℃, 110℃, 120℃, 130℃, 140℃ or 150℃.

[0065] The present invention purifies the crude product by column chromatography, using silica gel as the stationary phase and a mixed solvent of petroleum ether and ethyl acetate in a volume ratio of (10:1) to (20:1) as the eluent.

[0066] This invention utilizes a hydrogen transfer reaction strategy, eliminating the need for an external hydrogen source and enabling the efficient preparation of Guerbert alcohols under mild temperature conditions of 80-150°C. Compared to traditional high-temperature, high-pressure reaction conditions, this significantly reduces reaction energy consumption and equipment requirements, making the operation simpler and safer. Experimental results show that the hydrogen transfer catalyst of this invention achieves a conversion rate of over 95% for fatty alcohols and a selectivity of over 85% for Guerbert alcohols in the catalytic preparation reaction. Furthermore, the catalyst's catalytic activity and selectivity do not significantly decrease after five reuses.

[0067] To further illustrate the present invention, the following detailed description, in conjunction with embodiments, provides a composite hydrogen transfer catalyst based on MOFs materials, its preparation method, and its application. However, these descriptions should not be construed as limiting the scope of protection of the present invention.

[0068] Catalyst Preparation Examples

[0069] Example 1: Ru-supported hydrogen transfer catalyst based on UiO-66 (2 wt% loading)

[0070] (1) Pretreatment of UiO-66: Place UiO-66 powder in a vacuum drying oven and vacuum dry at 100℃ for 8 hours to remove moisture and impurities from the pores;

[0071] (2) Preparation of Ru precursor solution: Weigh 0.0527 g of ruthenium trichloride (RuCl3·3H2O), dissolve it in 100 mL of ethanol, and prepare a Ru precursor solution with a concentration of 0.00202 mol / L (Calculation: 0.0527 g ÷ 261.48 g / mol ÷ 0.1 L ≈ 0.00202 mol / L);

[0072] (3) Loading Ru active component: 1 g of pretreated UiO-66 was added to the above Ru precursor solution and stirred at room temperature for 4 h; then 0.05 g of sodium borohydride (NaBH4) was added dropwise to the mixed solution and stirred at 50 °C for 2 h.

[0073] (4) Separation and drying: The mixed solution was centrifuged (8000 rpm, 10 min) and the solid product was collected. The solid product was washed 4 times with deionized water and ethanol respectively. Then the solid product was placed in a vacuum drying oven and dried under vacuum at 70℃ for 8 h to obtain UiO-66 / Ru hydrogen transfer catalyst with Ru loading of 2 wt% (calculation: Ru mass = 0.0527g × 101.07 / 261.48≈0.0204g, loading = 0.0204g / (1g+0.0204g)×100%≈2.00%).

[0074] (5) Composite and activation: The UiO-66 / Ru hydrogen transfer catalyst and MgO were mixed at a mass ratio of 1:0.5 and ground for 2 hours using a planetary ball mill with agate balls as the grinding medium at a speed of 300 rpm. The mixed powder was then calcined at 120°C for 1.5 hours under N2 atmosphere to obtain the UiO-66 / Ru-2%+MgO composite hydrogen transfer catalyst.

[0075] Example 2: Pd-supported hydrogen transfer catalyst based on MIL-101 (2 wt% loading)

[0076] (1) Pretreatment of MIL-101: Place MIL-101 powder in a vacuum drying oven and vacuum dry at 100°C for 8 hours to remove moisture and impurities from the pores;

[0077] (2) Preparation of Pd precursor solution: Weigh 0.0343 g palladium chloride (PdCl2), dissolve it in 100 mL ethanol, and prepare a Pd precursor solution with a concentration of 0.00193 mol / L (Calculation: 0.0343 g ÷ 177.33 g / mol ÷ 0.1 L ≈ 0.00193 mol / L);

[0078] (3) Loading Pd active components: 1 g of pretreated MIL-101 was added to the above Pd precursor solution and stirred at room temperature for 4 h; then 0.05 g of sodium borohydride (NaBH4) was added dropwise to the mixed solution and stirred at 50 °C for 2 h.

[0079] (4) Separation and drying: Centrifugation (8000 rpm, 10 min), the solid product was washed 4 times with deionized water and ethanol, and vacuum dried at 70℃ for 8 h to obtain MIL-101 / Pd hydrogen transfer catalyst with a Pd loading of 2 wt% (calculation: Pd mass = 0.0343g × 106.42 / 177.33≈0.0204g, loading = 0.0204g / (1g+0.0204g)×100%≈2.00%).

[0080] (5) Composite and activation: MIL-101 / Pd hydrogen transfer catalyst and MgO were mixed at a mass ratio of 1:0.5, ball-milled (300 rpm, 2 h), and then calcined at 120 °C for 1.5 h under N2 atmosphere to obtain MIL-101 / Pd-2%+MgO composite hydrogen transfer catalyst.

[0081] Example 3: Ru-supported hydrogen transfer catalyst based on ZIF-8 (2 wt% loading)

[0082] (1) Pretreatment of ZIF-8: vacuum drying at 100℃ for 8 hours;

[0083] (2) Preparation of Ru precursor solution: Weigh 0.0527 g RuCl3·3H2O and dissolve it in 100 mL of ethanol to obtain a concentration of 0.00202 mol / L;

[0084] (3) Loading Ru active component: 1 g ZIF-8 was stirred with the precursor solution at room temperature for 4 h, 0.05 g NaBH4 was added, and stirred at 50 °C for 2 h;

[0085] (4) Separation and drying: centrifuge (8000 rpm, 10 min), wash 4 times, vacuum dry at 70℃ for 8 h to obtain ZIF-8 / Ru catalyst with Ru loading of 2 wt%;

[0086] (5) Composite and activation: The mixture was ball-milled with MgO at a ratio of 1:0.5 and calcined at 120°C for 1.5 h under N2 atmosphere to obtain ZIF-8 / Ru-2%+MgO composite catalyst.

[0087] Example 4: Pt-supported hydrogen transfer catalyst based on UiO-66 (loading 2 wt%)

[0088] (1) Pretreatment of UiO-66: vacuum drying at 100℃ for 8 hours;

[0089] (2) Preparation of Pt precursor solution: Weigh 0.0546 g of chloroplatinic acid (H2PtCl6·6H2O), dissolve it in 100 mL of ethanol, and prepare a Pt precursor solution with a concentration of 0.00105 mol / L (Calculation: 0.0546 g ÷ 517.91 g / mol ÷ 0.1 L ≈ 0.00105 mol / L);

[0090] (3) Loading Pt active component: 1 g UiO-66 was stirred with the precursor solution at room temperature for 4 h, 0.05 g NaBH4 was added, and stirred at 50℃ for 2 h;

[0091] (4) Separation and drying: Centrifuge (8000 rpm, 10 min), wash 4 times, and vacuum dry at 70℃ for 8 h to obtain UiO-66 / Pt catalyst with a Pt loading of 2 wt% (calculation: Pt mass = 0.0546g × 195.08 / 517.91≈0.0204g, loading = 2.00%).

[0092] (5) Composite and activation: Mix with MgO at a ratio of 1:0.5 and ball mill, then calcine at 120℃ in N2 atmosphere for 1.5h to obtain UiO-66 / Pt-2%+MgO composite catalyst.

[0093] Examples of the preparation and application of Gelbert alcohol

[0094] Example: Preparation of Guerbert alcohol by using a composite hydrogen transfer catalyst of ZIF-8 / Ru and solid base

[0095] (1) Construction of the reaction system: 100 g n-octanol (0.77 mol), 5 g toluene (mass ratio of n-octanol to toluene is 1:0.05) and 0.5 g ZIF-8 / Ru composite hydrogen transfer catalyst with solid base (catalyst amount is 0.5% of the mass of n-octanol) were added to a 500 mL reactor.

[0096] (2) Control of reaction conditions: Seal the reactor, purge the air with nitrogen 4 times, then place the reactor in an oil bath, heat it to 120°C with a stirring speed of 500 rpm, and the reaction time is 8 h;

[0097] (3) Separation and purification of the product: After the reaction was completed, the product was cooled to room temperature and filtered to separate the catalyst. The filtrate was collected and subjected to vacuum distillation at a vacuum of 0.09 MPa and a temperature of 120 °C. The crude product was purified by column chromatography (silica gel as the stationary phase and petroleum ether and ethyl acetate in a volume ratio of 15:1 as the eluent) to obtain the Gelbert alcohol product.

[0098] The conversion rate of n-octanol was 95.3%, the selectivity of guerbert alcohol was 85.7%, the yield was 81.5%, and the product purity was 98.0%.

[0099] The prepared catalysts were used in the reaction of n-octanol to prepare Guerbert alcohol, and the reaction conditions were consistent with the application examples above. The results are as follows:

[0100] Table 1: Catalytic performance of different catalyst types

[0101] Catalyst type raw material Reaction conditions Conversion rate (%) Selectivity (%) Yield (%) Product purity (%) Conversion rate (%) after repeating 5 times UiO-66 / Ru-2%+MgO Octyl alcohol 120℃,8h 97.5 88.3 86.0 98.5 95.2 MIL-101 / Pd-2%+MgO Octyl alcohol 120℃,8h 96.8 87.6 84.7 98.2 94.8 ZIF-8 / Ru-2%+MgO Octyl alcohol 120℃,8h 95.3 85.7 81.5 98.0 93.5 UiO-66 / Pt-2%+MgO Octyl alcohol 120℃,8h 94.5 84.3 79.5 98.5 92.1 UiO-66 / Ru-2%+CaO Octyl alcohol 120℃,8h 97.2 88.3 86.8 98.3 91.0 UiO-66 / Ru-2%+BaO Octyl alcohol 120℃,8h 95.0 87.5 82.1 98.1 90.2

[0102] As shown in Table 1 above, the hydrogen transfer catalysts of the present invention all have excellent catalytic effects on Guerbert alcohols, with conversion rates all above 94% and selectivity all above 84%, exhibiting the characteristics of high catalytic activity and good selectivity. In addition, the MOFs materials are preferably selected from MIL-101 or UiO-66, and the active metal components are preferably selected from ruthenium or palladium.

[0103] Catalyst reusability test (taking UiO-66 / Ru-2%+MgO as an example)

[0104] The separated catalyst was repeatedly used in the reaction to prepare Guerbert alcohol from n-octanol, with each reaction under the same conditions as in the application examples described above. The results are as follows:

[0105] Table 2: Effect of Catalyst Reuse

[0106] Number of times to reuse Octyl alcohol conversion rate (%) Goerbert alcohol selectivity (%) Goerbert alcohol yield (%) 1 97.5 88.3 85.7 2 97.8 87.9 85.4 3 96.5 87.5 82.5 4 95.8 86.8 81.8 5 95.2 86.2 81.2

[0107] As shown in Table 2 above, after five reuses, the hydrogen transfer catalyst of the present invention still maintains a conversion rate of over 95% for n-octanol, a selectivity of over 86% for guerbert alcohol, and a yield of over 81% for guerbert alcohol, indicating that the catalyst has excellent reusability.

[0108] Catalytic performance of the catalyst on hydrogen transfer of other fatty alcohols (taking UiO-66 / Ru-2%+MgO as an example)

[0109] Example: Using n-decyl alcohol as raw material, Gerbert alcohol was prepared by catalysis using a composite hydrogen transfer catalyst of UiO-66 / Ru-2% and solid base.

[0110] (1) Construction of the reaction system: 125 g n-decanol (0.77 mol), 6.25 g toluene (mass ratio of n-decanol to toluene is 1:0.05) and 0.5 g UiO-66 / Ru-2%+MgO composite hydrogen transfer catalyst (catalyst amount is the same as above) were added to a 500 mL reactor.

[0111] (2) Control of reaction conditions: Seal the reactor, purge the air with nitrogen 4 times, then place the reactor in an oil bath, heat it to 120°C with a stirring speed of 500 rpm, and the reaction time is 8 h;

[0112] (3) Separation and purification of the product: After the reaction was completed, the product was cooled to room temperature and filtered to separate the catalyst. The filtrate was collected and subjected to vacuum distillation at a vacuum of 0.09 MPa and a temperature of 150 °C. The crude product was purified by column chromatography (silica gel as the stationary phase and petroleum ether to ethyl acetate in a volume ratio of 15:1 as the eluent) to obtain the Gerbert alcohol product (2-octyldodecyl alcohol).

[0113] The conversion rate of n-decyl alcohol was 97.3%, the selectivity of Guerbert alcohol was 89.6%, the yield was 86.1%, and the product purity was 98.0%.

[0114] As shown in the above embodiments, this invention provides a composite hydrogen transfer catalyst based on MOFs materials, comprising MOFs materials supported with an active metal component and a solid base; the active metal component is selected from at least one of palladium, platinum, ruthenium, rhodium, and nickel; the active metal component accounts for 0.5-5% of the catalyst mass; the MOFs material is selected from at least one of ZIF-8, MIL-101, UiO-66, HKUST-1, and MOF-5; the solid base is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite, and barium oxide. The catalyst provided by this invention has advantages such as high catalytic activity, good selectivity, strong stability, and reusability. It can efficiently catalyze the hydrogen transfer reaction of fatty alcohols to prepare Guerbert alcohols under temperature reaction conditions, significantly improving product yield and purity, and reducing reaction energy consumption and cost. Experimental results show that in the catalytic preparation of Guerbert alcohols, the hydrogen transfer catalyst of this invention achieves a fatty alcohol conversion rate of over 95% and a Guerbert alcohol selectivity of over 85%, and after five reuses, its catalytic activity and selectivity do not significantly decrease.

[0115] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A composite hydrogen transfer catalyst based on MOFs materials, comprising MOFs materials supported on active metal components and a solid base; The active metal component is selected from at least one of palladium, platinum, ruthenium, rhodium, and nickel; the active metal component accounts for 0.5% to 5% of the catalyst mass; The MOFs material is selected from at least one of ZIF-8, MIL-101, UiO-66, HKUST-1, and MOF-5; The solid alkali is selected from at least one of magnesium oxide, calcium oxide, hydroxyapatite, and barium oxide.

2. The composite hydrogen transfer catalyst based on MOFs materials according to claim 1, characterized in that, The mass ratio of the solid alkali to the MOF material loaded with active metal components is (1:0.1) to (1:1).

3. The composite hydrogen transfer catalyst based on MOFs materials according to claim 1, characterized in that, The active metal component is selected from ruthenium or palladium; The MOFs material is selected from MIL-101 or UiO-66.

4. A method for preparing a composite hydrogen transfer catalyst based on MOFs materials as described in any one of claims 1 to 3, comprising the following steps: After drying the MOF material, it was mixed with an active metal precursor solution and stirred at room temperature for 2-6 hours. Then, a reducing agent was added, and the mixture was stirred at 30-60°C for 1-3 hours. After separation, a solid product was obtained. The solid product was washed, then vacuum dried and activated to obtain a hydrogen transfer catalyst based on MOFs materials. The MOF-based hydrogen transfer catalyst is mixed with a solid base, ball-milled or ground, and then activated to obtain a MOF-based composite hydrogen transfer catalyst.

5. The preparation method according to claim 4, characterized in that, The reducing agent is selected from one or more of sodium borohydride, hydrazine hydrate, and formaldehyde.

6. The preparation method according to claim 4, characterized in that, The concentration of the active metal precursor solution is 0.001~0.1 mol / L; The active metal precursor is selected from at least one of palladium chloride, chloroplatinic acid, ruthenium trichloride, rhodium chloride, and nickel nitrate.

7. The preparation method according to claim 4, characterized in that, The activation temperature is 100~150℃, and the activation time is 1~2h.

8. A method for preparing Guerbert alcohol using the composite hydrogen transfer catalyst based on MOFs materials as described in any one of claims 1 to 3, comprising the following steps: Fatty alcohol, solvent and MOF-based composite hydrogen transfer catalyst were mixed, and the air was replaced with nitrogen. The mixture was reacted at 80-150℃ for 4-12 h. After the reaction was completed, the mixture was cooled, separated, and the collected filtrate was distilled under reduced pressure to obtain the crude product. After purification, Goerbert alcohol was obtained.

9. The method according to claim 8, characterized in that, The fatty alcohol is selected from one or more of n-hexanol, n-octanol, n-decanol, n-dodecanol, and n-tetradecylol; The mass ratio of the fatty alcohol to the solvent is (1:0.01) to (1:1).

10. The method according to claim 8, characterized in that, The vacuum degree of the vacuum distillation is 0.08~0.095MPa, and the temperature is 100~150℃; Purification was performed using silica gel as the stationary phase and a mixture of petroleum ether and ethyl acetate in a volume ratio of (10:1) to (20:1) as the eluent.

Citation Information

Patent Citations

  • Method for preparing Guerbet alcohol

    CN101659597A

  • Process for the production of Guerbet alcohols

    US5777183A

  • Method for producing Guerbet alcohols

    US8779216B2

Cited By

  • Preparation method of a composite modified tertiary amine catalyst

    CN122377546A